Balloon aortic valvoplasty in paediatric patients: progressive aortic regurgitation is common. Issue 1 (15th December 2003) - Balmer, C; Beghetti, M; Fasnacht, M; Friedli, B; Arbenz, U
Abstract : Objective: To evaluate immediate and midterm results after balloon valvoplasty in a paediatric population with congenital aortic stenosis, giving special consideration to aortic regurgitation. Design: Retrospective study. Setting: Two tertiary referral centres for paediatric cardiology. Patients: 70 consecutive patients, with an age range of 0–16.4 years. Group A infants < 3 months old (n = 21). Group B children > 3 months old (n = 49). Median follow up time was 19.8 months, range 0–158 months. Intervention: All patients underwent balloon aortic valvoplasty. The balloon to annulus ratio was selected at a mean of 0.90 (range 0.67–1.0). Main outcome measures: Doppler gradients and degree of aortic regurgitation. Results: The pressure gradient dropped significantly with the intervention and increased mildly at follow up. Freedom from relevant aortic regurgitation (that is, moderate and severe) was initially lower in group A (75% v 90% after one month) but after two years the difference between the two groups was not significant (50% v 61%). Freedom from reintervention was significantly lower in group A (with 35% v 80%) after three years. Conclusion: Aortic balloon valvoplasty is safe and effective but has a high rate of early reintervention in infants with critical aortic stenosis. The major long term problem is progressive aortic regurgitation, which does not seem to be prevented by the use of small balloons.